COMMUNITY-BASED ECOTOURISM DEVELOPMENT: THE BOJO ALOGUINSAN ECOTOURISM ASSOCIATION (BAETAS) CASE IN ALOGUINSAN, CEBU, PHILIPPINES - Alburo, Hemres M; Alburo, Rosalyn P; Cutillas, Anesito L; Pinote, Juanita P (Journal of Agriculture and Technology Management, 2018)
Participatory development has been used as a common framework of governance today. It is envisioned to tap human resources outside the traditional government-run or pure private sector operated development initiatives, believing that communities are capable of handling economic endeavors with proper training and start up investments. Under this framework, an assessment of a community-based ecotourism development initiative in the town of Aloguinsan in western Cebu was made to highlight its beginning, success stories, challenges met and its way forward, with the rapidly changing priorities and leadership of local politics. Key respondent interviews and actual field observations were made to gather data. Results show that the Bojo Aloguinsan Ecotourism Association (BAETAS) arose from the program of the Cebu Provincial Government's "Suroy-suroy Sugbu" (Tour Cebu), which encouraged participating municipalities to showcase their tourism potential. The municipal government provided the seed money of P1 Million as start up capital to develop the Bojo river. BAETAS is run by a group of fishermen and housewives, who facilitate a river tour, which includes on-site ecological lectures on mangroves and birds, handy cradt making demo and a serenaded lunch. Over years of operation BAETAS has provided an alternative livelihood of its members and has helped promote the town of Aloguinsan. The uniqueness of the area and the community running it makes the destination admirable. With the community having the sense of ownership of the program, changing political leadership can be viewed to have minimal impacts on the project.